Analisis Penggunaan Model PhBL pada Teori Newton untuk Meningkatkan Kreativitas Mahasiswa Pendidikan Fisika - Himsar Himsar (Institut Agama Islam Negeri Padangsidimpuan, 2026)
This research stems from the fact that learning has not yet been able to accommodate theory with real-life facts. Nowadays, students focus on AI media that instantly provide answers. AI media cannot be fully relied upon because it cannot distinguish between opinion and fact. Newton's theory is a concept closely tied to nature and everyday activities, so there needs to be a solution for this material. The PhBL model is a learning model connected to daily life and is very suitable to be applied. The research method used is Mixed Method with a content analysis approach. The sample in this research is third-semester students taking the Mechanics course. The connection between the PhBL model and Newton's theory is very close and directly related to real-life facts. The PhBL model syntax involves 6 steps: phenomenon orientation, formulating questions, organizing in learning, investigation, analysis and synthesis, and presenting results.These 6 steps are integrated into Newton's theory to become a complete concept. Students are interested in learning Newton's Theory with the PhBL model.